Base mediated synthesis of functionalized 2-(alkynyl)arylnitriles and their molecular docking study with aromatase receptor. Issue 15 (29th March 2021) - Shah, Chandan; Yadav, Pratik; Althagafi, Ismail; Nemaysh, Vishal; Shaw, Ranjay; Elagamy, Amr; Pratap, Ramendra
Abstract : Synthesis of 2-alkynyl-arylnitriles has been reported by a ring transformation approach. Abstract : A simple, efficient, and transition metal-free approach to synthesize functionalized 2-(alkynyl)benzonitriles has been developed using suitably functionalized 2 H -pyran-2-ones and 4-phenyl/trimethylsilanyl-but-3-yn-2-ones as precursors. The reaction proceeds in the presence of a base at room temperature to yield internal as well as terminal alkynes. The structure of the synthesized compound was confirmed by single-crystal X-ray analysis. The molecular docking study was performed to evaluate the binding mode of action of newly synthesized alkyne derivatives with known human breast cancer target receptor aromatase (PDB ID: ; 3EQM ).